(untitled) (Altre Modernità, 2016)
In one of his last appearances as presenter of Newsnight (BBC 20 May 2014), veteran journalist Jeremy Paxman interviewed Silvio Berlusconi. Three minutes into the voiced-over interpreter-mediated dialogue, the journalist known as "Newsnight’s Rottweiler-in-chief" asked: "Is it true you called [Angela Merkel] an unfuckable lardarse?" Momentarily flustered, Berlusconi toyed with the earpiece from which he listened to the interpreter translate. Recomposing himself he replied: "Non ho mai, in venti anni di politica, insultato nessuno", [I have never, in twenty years of politics, insulted anyone]. While the veracity of Berlusconi’s response is debateable, the issues at stake in this contribution are others. Combining approaches from ethnomethodology with critical discourse analysis (CDA), the article examines three aspects of the communicative event. The first focuses on its technical and linguistic construction, and the (instrumental?) choice of voice-over actor. The second aspect asks what pprompted the BBC’s decision to air the offending language, albeit through translation. Jeremy Paxman’s views on the role of interpreting and voiceover in the construction of the interview were sought, providing insight on the social actor’s perspective. The third aspect relates to the discursive construction of the event and outlines the intertextual chains (Fairclough 1995) it generated. A small dataset of British newspaper articles on the interview is analysed. Finally, the contribution offers some closing remarks.